Protective HLA class I Alleles That Restrict Acute-Phase CD8+ T-Cell Responses Are Associated with Viral Escape Mutations Located in Highly Conserved Regions of Human Immunodeficiency Virus Type 1 - Wang, Yaoyu E.; Li, Bin; Carlson, Jonathan M.; Streeck, Hendrik; Gladden, Adrianne D.; Goodman, Robert; Schneidewind, Arne; Power, Karen A.; Toth, Ildiko; Frahm, Nicole; Alter, Galit; Brander, Christian; et al. (Journal of Virology, 2009)
The control of human immunodeficiency virus type 1 (HIV-1) associated with particular HLA class I alleles suggests that some CD8+ T-cell responses may be more effective than others at containing HIV-1. Unfortunately, substantial diversities in the breadth, magnitude, and function of these responses have impaired our ability to identify responses most critical to this control. It has been proposed that CD8 responses targeting conserved regions of the virus may be particularly effective, since the development of cytotoxic T-lymphocyte (CTL) escape mutations in these regions may significantly impair viral replication. To address this hypothesis at the population level, we derived near-full-length viral genomes from 98 chronically infected individuals and identified a total of 76 HLA class I-associated mutations across the genome, reflective of CD8 responses capable of selecting for sequence evolution. The majority of HLA-associated mutations were found in p24 Gag, Pol, and Nef. Reversion of HLA-associated mutations in the absence of the selecting HLA allele was also commonly observed, suggesting an impact of most CTL escape mutations on viral replication. Although no correlations were observed between the number or location of HLA-associated mutations and protective HLA alleles, limiting the analysis to mutations selected by acute-phase immunodominant responses revealed a strong positive correlation between mutations at conserved residues and protective HLA alleles. These data suggest that control of HIV-1 may be associated with acute-phase CD8 responses capable of selecting for viral escape mutations in highly conserved regions of the virus, supporting the inclusion of these regions in the design of an effective vaccine.